Why Soviet Russia is starving - Tyrkova-Williams, Ariadna (London : Russian Liberation Committee, 1919)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: bolsjewisme; voedseldistributie; Sovjet-Unie.